Brokering Europe : Euro-lawyers and the making of a transnational polity - Vauchez, Antoine (Cambridge studies in European law and policy., 2015)
"Ever since the 1960s onwards, the nature and the future of the European Union have been defined in legal terms. Yet, we are still in need of an explanation as to how this entanglement between Law and EU polity-building emerged and how it was maintained over time. While most of the literature offers a disembodied account of European legal integration, Brokering Europe reveals the multifaceted roles Euro-lawyers have played in EU polity, notably beyond the litigation arena. In particular, the book points at select transnational groups of multipositioned legal entrepreneurs which have been in a situation to elevate the role of law in all sorts of EU venues. In doing so, it draws from anew set of intellectual resources (field-theory) and empirical strategies only very recently mobilized for the study of the EU. Grounded on an extensive historical investigation, Brokering Europe provides a revised narrative of the 'constitutionalization of Europe'"--